Peningkatan Hasil Belajar Peserta Didik dalam Pembuatan Ragam Hias Motif Batik Tanah Liek Menggunakan Model Project Based Learning Kelas V SDN 08 Sungai Rumbai Kabupaten Dharmasraya (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
This study aims to improve students’ learning outcomes in creating decorative patterns of Batik Tanah Liek through the application of the Project Based Learning (PjBL) model in Grade V at SDN 08 Sungai Rumbai, Dharmasraya Regency. The type of research used is Classroom Action Research (CAR) conducted in two cycles. The research subjects were 20 fifth-grade students. Data were collected through observation, learning outcome tests, and skills assessments, and analyzed using descriptive quantitative and qualitative analysis techniques. The results showed an improvement in every assessment aspect from cycle I to cycle II. The teaching module score increased from 75.00% in cycle I to 90.00% in cycle II. Teacher activity increased from 80.00% to 93.33%. Student activity improved from 78.33% to 91.67%. The skill assessment also showed a significant increase from 72.50% to 87.50%. Based on these results, it can be concluded that the implementation of the Project Based Learning (PjBL) model is effective in enhancing teacher engagement, student activeness, the quality of the teaching module, and students’ skills in creating decorative patterns of Batik Tanah Liek. This model provides students with opportunities to create, collaborate, and apply visual arts knowledge in real-life contexts.